In vitro Antibacterial Activities of Nepeta transcaucasica - Ozturk, A. (Asian Journal of Chemistry, 2010)
The present results showed that the methanol extract of the Nepeta transcaucasica had antibacterial activity against 14 out of 50 bacteria with inhibition zone between 8-13 mm. The plant extract found to be more active against Corynebacterium ammoniagenes. Some of the extracts had the lowest MIC values (31.25 μg/mL) compared the standard drug, maxipime indicating the plant had an important natural antimicrobial source. These results also support the traditional use of this plant in folk medicine by local peoples living in rural areas in Turkey.